Influence of electron-beam irradiation on surface properties of magnetic iron oxide nanoparticles stabilized with citrate. (April 2020) - Duszyńska, Angelika; Danielewicz, Agnieszka; Kadłubowski, Sławomir; Kozanecki, Marcin; Maniukiewicz, Waldemar; Sowiński, Przemysław; Szadkowska – Nicze, Magdalena
Abstract: Influence of electron beam (EB) irradiation on surface properties of magnetite was investigated using XRD, TEM, DLS, zeta-potential, FTIR and Raman spectroscopy. Fe3 O4 particles were synthesized by alkaline hydrolysis of ferrous ions and stabilized with sodium citrate. Dry samples of bare and citrate- coated Fe3 O4 particles were EB-irradiated with doses up to 300 kGy. The crystallite sizes of uncoated and citrate-coated magnetite were found to be in the range of 25–27 nm and 30–32 nm, respectively. EB- irradiation did not result in phase and size change of Fe3 O4 nanoparticles. Using DLS and TEM analysis, it has been found, that EB-irradiated bare Fe3 O4 nanoparticles have aggregated in aqueous dispersion. Traces of hematite and maghemite were identified on the surface of EB-irradiated bare particles by Raman spectroscopy. Radiation-induced oxidation of magnetite was probably involved to radiolysis of water molecules adsorbed onto particle surface and formation of hydroxyl radicals which are strong oxidize species. Disaggregation of citrate-coated particles in water dispersion after EB irradiation has been assigned to disruption of Fe-citrate bonds. Highlights: Magnetite particles, after separation from reaction mixture and drying, were irradiated using electron beam (EB). After EB irradiation bare Fe3 O4 nanoparticles aggregated in aqueous dispersion. Surface of uncoated Fe3 O4 particles was oxidized during EB irradiation. EB irradiation caused disaggregation of citrate-coated Fe3 O4 particles.